The Interactive Multimedia Learning Application for Visual Communication Classroom - Arje Cerullo Djamen; Johan Reimon Batmetan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Interactive multimedia is an excellent choice in online learning during the COVID-19 pandemic. Building attractive, interactive multimedia requires special skills and an established framework, so many teachers find it difficult to build it. This study aims to explain the implementation of an integrated interactive multimedia framework in the learning process and the techniques used to build learning media. We explain the integration of the multi-media framework between the components of the learning environment, behavioral activity, cognitive/metacognitive activity. We implemented these three components in visual communication learning and managed to build an interactive multimedia learning media that can truly represent all the components of learning in schools. We conclude that the integration of the three components results in an interactive learning media that has good quality in the learning process.